2021
DOI: 10.1021/jacs.1c04417
|View full text |Cite
|
Sign up to set email alerts
|

A Cyaphide Transfer Reagent

Abstract: The cyanide ion plays a key role in a number of industrially relevant chemical processes, such as the extraction of gold and silver from low grade ores. Metal cyanide compounds were arguably some of the earliest coordination complexes studied and can be traced back to the serendipitous discovery of Prussian blue by Diesbach in 1706. By contrast, heavier cyanide analogues, such as the cyaphide ion, CP − , are virtually unexplored despite the enormous potential of such ions as ligands in coordination compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 47 publications
(103 reference statements)
1
53
0
6
Order By: Relevance
“…Examples are the development of [PCO] − chemistry in the last few decades [1] and the recent report of a [CP] − transfer reagent. [2] The chemistry of compounds with an NCN [3] unit such as in cyanamides like Ca[N=C=N] produced on large scale, or carbodiimides, [4] or species containing an NCC group [5] is well‐established. In contrast, compounds with a PCN sequence are comparatively little investigated.…”
mentioning
confidence: 99%
“…Examples are the development of [PCO] − chemistry in the last few decades [1] and the recent report of a [CP] − transfer reagent. [2] The chemistry of compounds with an NCN [3] unit such as in cyanamides like Ca[N=C=N] produced on large scale, or carbodiimides, [4] or species containing an NCC group [5] is well‐established. In contrast, compounds with a PCN sequence are comparatively little investigated.…”
mentioning
confidence: 99%
“…In 2021, Goicoechea et al reported the synthesis and isolation of magnesium–cyaphido complexes by the reduction of i Pr 3 SiOCP using a magnesium( i ) reagent. 27 The reaction of i Pr 3 SiOTf with [Na(dioxane) x ](OCP) gave the silylation product i Pr 3 SiOCP. Further addition of Jones’ magnesium( i ) reagent [Mg( Dipp NacNac)] 2 29 a , b to i Pr 3 SiOCP afforded an equimolar mixture of [Mg( Dipp NacNac)(CP)(dioxane)] ( 1 ) and [Mg( Dipp NacNac)(OSi i Pr 3 )(dioxane)] ( 2 ; Dipp NacNac = CH{C(CH 3 )N-(Dipp)} 2 and Dipp = 2,6-di(isopropyl)phenyl), which were isolated at low temperature (Scheme 3).…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 99%
“…9,10 One rationale for their instability is the weak nature of the phosphaalkyne (CP) bond. 8,11 Because s-block elements are highly oxophilic, they favor the oxyphosphaalkyne isomer (i.e., − O−CP), whereby the OCP anion is prone to decomposition through oxidation and selfoligomerization. 1,8 The highly electropositive character of sodium and potassium cations allows for pronounced charge separation in their M(OCP) salts, which results in increased Coulombic repulsion between the OCP anions and discourages oligomerization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast to the stability and versatility of sodium and potassium phosphaethynolate complexes, their group 2 counterparts (Mg, Ca, Sr, and Ba) are unstable in solution and thus difficult to study. , One rationale for their instability is the weak nature of the phosphaalkyne (CP) bond. , Because s-block elements are highly oxophilic, they favor the oxyphosphaalkyne isomer (i.e., – O–CP), whereby the OCP anion is prone to decomposition through oxidation and self-oligomerization. , The highly electropositive character of sodium and potassium cations allows for pronounced charge separation in their M­(OCP) salts, which results in increased Coulombic repulsion between the OCP anions and discourages oligomerization . The “free” OCP anion in these complexes is stabilized by delocalization of electron density from O to CP π*, thereby reducing the bond order and consequent reactivity of the C–P bond and concomitantly increasing the bond order and thermodynamic stability of the C–O bond.…”
Section: Introductionmentioning
confidence: 99%